« Little grunts, the grins and grimaces of recognition »: Resistance and Exchange in Paul Muldoon and Norman MacBeath’s Plan B - Alexandra Tauvry (Revue LISA)
A significant part of Paul Muldoon’s recent work has been dedicated to experimenting with the visual arts and, in particular, photography. He recently published a book with Scottish photographer Norman McBeath entitled Plan B (2009). This work presents us with a new genre: photoetry. In fact, in a foreword to the book, Muldoon explains that the poems and photographs are “making all sorts of connections of their own, none right-in-your-face […] yet all somehow revelatory, all accompanied by little grunts, the grins and grimaces of recognition.” However, although this work confronts poems with photographs in praesentia, Muldoon increasingly resorts to the literary device of ekphrasis in order to exploit the work of photographers. Muldoon’s poetry is sometimes akin to a palimpsest, a repository of words and concealed images, which only appear beneath the surface, in absentia.